2018
DOI: 10.18632/oncotarget.25782
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine contributes to cellular phenotype in a genetically-defined model of breast cancer progression

Abstract: The mRNA modification N6-methyladenosine (m6A) is involved in many post-transcriptional regulatory processes including mRNA stability and translational efficiency. However, it is also imperative to correlate these processes with phenotypic outputs during cancer progression. Here we report that m6A levels are significantly decreased in genetically-defined immortalized and oncogenically-transformed human mammary epithelial cells (HMECs), as compared with their primary cell predecessor. Furthermore, the m6A methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…METTL14, a key component of the m6A methyltransferase complex, has been reported to be dysregulated and play critical roles in the tumorigenesis of glioblastoma, 28 AML, 33 and breast cancer. 34 At present, the studies on the role of m6A modification in CRC remain elusive. Bai et al 35 reported that YTH m6A RNA binding protein 1 (YTHDF1) is a core factor in RNA methylation modification and plays a vital oncogenic role in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…METTL14, a key component of the m6A methyltransferase complex, has been reported to be dysregulated and play critical roles in the tumorigenesis of glioblastoma, 28 AML, 33 and breast cancer. 34 At present, the studies on the role of m6A modification in CRC remain elusive. Bai et al 35 reported that YTH m6A RNA binding protein 1 (YTHDF1) is a core factor in RNA methylation modification and plays a vital oncogenic role in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…m 6 A modification is the most prevalent chemical modification carried by cellular RNAs. The m 6 A has been implicated in tumorigenesis, due to its capacity of regulating RNA splicing, translocation, stability, and translation (Chen et al, 2018; Chen et al, 2019; Fry et al, 2018; He et al, 2018; Ianniello & Fatica, 2018; Li et al, 2018; Liu et al, 2018; Liu et al, 2018). However, the knowledge of m 6 A modification remains preliminary in the cancer field, especially in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To date, this type of chemical modification of RNA has been involved in a broad spectrum of cancer types (Chen et al, 2018; Chen, Zhang, & Zhu, 2019; Fry et al, 2018; He et al, 2018; Ianniello & Fatica, 2018; Liu et al, 2018; Liu et al, 2018), especially acute myeloid leukemia (AML), glioblastoma, hepatocellular carcinoma (HCC), and breast cancer. Some studies have reported abnormal m 6 A status in lung cancer (Du et al, 2017; Lin, Choe, Du, Triboulet, & Gregory, 2016; Liu et al, 2018); however, the implications of m 6 A RNA modification regulators in NSCLC are mainly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly evidence showed that the levels and effects of m6A in tumor cells change continuously as the tumor progresses. For instance, changes in cellular m6A levels can alter the phenotypes of breast cancer cells [ 60 ] and the malignancy of gastric cancer [ 61 ].…”
Section: Opposite Roles Of M6a In Tumorigenesismentioning
confidence: 99%